Full genomic sequence of the HLA‐C*07:308 allele identified by next generation sequencing. (28th February 2022) - Liacini, Abdelhamid; Peters, Lindsey; Gravante, Christopher; Mancini, Shannon; Geier, Steven
Abstract : Full‐length sequence of HLA‐C*07:308 covers the 5′‐untranslated region (UTR), all introns and exons and the 3′ UTR.